A Model for Predicting Temperature Produced by Upward Spreading Cable Fire under Natural Ventilation. (2015) - Huang, Xianjia; Bi, Kun; Liu, Xiaoshuang; Yi, Jianxin; Jiang, Xi
Abstract: This study aims at a better understanding of the temperature characteristics for vertical cable tray fire in a naturally ventilated compartment. Based on the assumption that the ceiling jet flow entrains hot gas from the upper smoke layer, a model has been proposed to predict the temperature of the jet flow for vertical cable fire. Unlike the existing models, the effect of upward spreading flame on the temperature was taken into account. Fire experiments were conducted under different cable layouts to examine the model. Good agreement between the temperature predicted by the model and the experimental results was achieved, despite that the fire behaviour varied significantly with the cable spacing.